Neon diffusion kinetics in olivine, pyroxene and feldspar: Retentivity of cosmogenic and nucleogenic neon - Gourbet,L; Shuster,DL; Balco,G; Cassata,WS; Renne,PR; Rood,D (Geochimica Et Cosmochimica Acta, 2012)
We performed stepwise degassing experiments by heating single crystals of neutron- or proton-irradiated olivine, pyroxene and feldspar to study diffusion kinetics of neon. This is important in evaluating the utility of these minerals for cosmogenic 21Ne measurements and, potentially, for Ne thermochronometry. Degassing patterns are only partially explained by simple Arrhenius relationships; most samples do not exhibit a precisely-determined activation energy in an individual diffusion domain. Regardless, we find clear differences in diffusion kinetics among these minerals. Based on sub-selected data, our estimates for neon diffusion kinetics (activation energy E a and pre-exponential factor D o, assuming the analyzed fragments approximate the diffusion domain) in each mineral are as follows: for the feldspars, E a ranges from ~65 to 115kJ/mol and D o from 3.9×10 -3 to 7.1×10 2cm 2s -1; for the pyroxenes, E a ranges from ~292 to 480kJ/mol and D o from 1.6×10 2 to 2.9×10 11cm 2s -1; for the olivines, E a ranges from ~360 to 370kJ/mol and D o from 1.5×10 6 to 5.0×10 6cm 2s -1. Differences in these parameters are broadly consistent with the expected effect of structural differences between feldspar, and olivine and pyroxene. These results indicate that cosmogenic 21Ne will be quantitatively retained within olivine and pyroxene at Earth surface temperatures over geological timescales. The diffusion kinetics for feldspars, on the other hand